Comparative leaf and wood anatomical characteristics of Chrysophyllum (Sapotaceae) relate to taxonomy of the species in Thailand - SAMOESAK PRASAWANG; Anitthan Srinual (Society for Indonesian Biodiversity, 2020)
Abstract. Prasawang S, Srinual A. 2020. Comparative leaf and wood anatomical characteristics of Chrysophyllum (Sapotaceae) relate to taxonomy of the species in Thailand. Biodiversitas 21: 1578-1587. Anatomical attributes are important tools for taxonomic studies of plants. The present study compared anatomical characteristics (i.e. lamina, petiole and wood) of two species of Chrysophyllum (namely Chrysophyllum cainito L. and C. roxburghii G.Don) belonging to family Sapotaceae in Thailand to develop taxonomic identification keys for two species of Chrysophyllum. Peeling and clearing methods were used for epidermal study, paraffin method for lamina and petiole transverse sections and standard microtome sectioning for anatomical analyses of wood. The findings of this study demonstrated the leaf and wood anatomical features presenting in C. cainito differs from those in the species of C. roxburghii including 1) shape and outline of epidermal cell wall 2) presence or absence of T-shaped trichome 3) presence or absence of inclusions 4) shape of vascular bundle and accessory bundle in midrib 5) shape of petiole and vascular bundle 6) grouping type of vessel 7) type of axial parenchyma 8) presence or absence of inclusions in rays and 9) thickness of fiber walls. Therefore, these characteristics can be used valuably as additional data in case of taxonomic studies of Thai Chrysophyllum.